Photonic Crystals for Plasmonics: From Fundamentals to Superhydrophobic Devices - Zaccaria, Remo Proietti; Gopalakrishnan, Anisha; Das, Gobind; Gentile, Francesco; Haddadpour, Ali; Toma, Andrea; Angelis, Francesco De; Liberale, Carlo; Mecarini, Federico; Razzari, Luca; Giugni, Andrea; Krahne, Roman; et al. (IntechOpen, 2012)
None